Following Islamic teachings in the governance of Islamic society with an emphasis on transparency - Rastgar, Abbas Ali (HTS teologiese studies, 2023)
Government is a rational necessity for mankind because a society without government leads to chaos. Government regulates the affairs of the individual and the community, implements the limits, and ensures the dignity and independence of the human society. Thinking in the main goals of the divine prophets, it is clear that achieving great goals such as liberating people from the domination and captivity of foreigners, comprehensive human education, reviving human values, establishing justice, bringing people to excellence and growth, etc., requires formation. In this context, transparency is a key attribute, which can bring much power to the expected level as an effective mechanism for protecting citizens’ political, economic, social and cultural rights. This concept is thus a valuable solution in the fight against sinister phenomena, such as political and economic corruptions, which are ranked as the biggest challenges facing any society. Even though transparency is nowadays deemed an emerging concept, its roots can be traced back to Islamic teachings, mainly during the short reign of Imam Ali, (peace be upon him [PBUH]). As a central figure, Imam Ali considered transparency as essential, and shared his views on governance and practical methods with the people and all audiences based on complete honesty and openness. As per Alavi thoughts, some criteria and indicators, both structural and behavioural, are involved in order to ensure the public good and meet the interests of all by providing the prerequisites for the realisation of transparency, at odds with the predominant ideas that transparency in governance, like many concepts in the political and governance-related spheres, has a western origin.Contribution: The concept of transparency, with a proven history in global experiences, accordingly holds a special place in the literature of Islamic governments. Given the importance of this topic, the present study with an emphasis on transparency aims to examine Islamic teachings on governance in Islamic societies, and reflect on governance transparency components in such societies, relying on expert opinions.